Chemical Characterization of Major and Minor Compounds of Nut Oils: Almond, Hazelnut, and Pecan Nut - Gabriel D. Fernandes; Raquel B. Gómez-Coca; María del Carmen Pérez-Camino; Wenceslao Moreda; Daniel Barrera-Arellano (Journal of Chemistry)
The aim of this work was to characterize the major and minor compounds of laboratory-extracted and commercial oils from sweet almond, hazelnut, and pecan nut. Oils from sweet almond, hazelnut, and pecan nut were obtained by means of an expeller system, while the corresponding commercial oils were provided from Vital Âtman (BR). The contents of triacylglycerols, fatty acids, aliphatic and terpenic alcohols, desmethyl-, methyl-, and dimethylsterols, squalene, and tocopherols were determined. Oleic, palmitic, and linoleic acids were the main fatty acids. Desmethylsterols were the principal minor compounds with β-sitosterol being the most abundant component. Low amounts of aliphatic and terpenic alcohols were also found. The major tocopherol in hazelnut and sweet almond oils was α-tocopherol, whereas γ-tocopherol prevailed in pecan nut oil. Principal component analysis made it possible for us to differentiate among samples, as well as to distinguish between commercial and laboratory-extracted oils. Heatmap highlighted the main variables featuring each sample. Globally, these results have brought a new approach on nut oil characterization.